Análise da disponibilidade hídrica da região hidrográfica do Tapajós como ferramenta de suporte à decisão para a outorga de recursos hídricos - ROCHA, Gabrielle Souto da (Universidade Federal do Pará, 2019)
This work presents an analysis of the water availability in the Tapajós hydrographic region, located in the state of Pará. For the analysis of the availability, the data of the historical series of the fluviometric stations of Tapajós RH were analyzed, considering a period of 20 years (1987-2007). such as grant information and waivers granted to users of water resources in the region. After the analysis of the fluviometric series, the reference curves were obtained with the Siscah 1.0 program to determine the reference flows Q90 and Q95. The program was also used to perform the statistical calculations to obtain Q7,10 for each fluviometric station. For the determination of the sub-basins and drainage area to obtain the remaining flows, the Otto Pfafstetter method was used, detailing up to level 4. Observing the presented results, it was verified that for the reference flows Q90 and Q95 for one maximum flow rate of 70%, for each method, the remaining flow in the sub-basins does not constitute a scenario of scarcity or water stress, while Q7,10 presented a criticality scenario for the applicable uses. In relation to the uses granted in the Tapajós hydrographic region, it was verified that the municipalities with the highest number of granted processes are Itaituba and Jacareacanga, and the highest number of grant exemptions is distributed between the municipalities of Itaituba and Rurópolis. It was identified that the use of water resources for Tapajós hydrographic region, based on the purposes of granting and dispensing of requested concessions, is for the service of earthworks, compaction and wetting of roads in the region. These uses are directly linked to the expansion of the region through works such as ports, hydroelectric power stations and opening of new avenues to increase the flow of agricultural products.